Measuring the Organizational Performance in the Government Departments of Dubai Using the Knowledge Management Process (European Journal of Social Science Education and Research, 2022)
In the latest years, the term knowledge management popped up frequently in government and private sector meetings. They expanded the horizon of the term and involved it in intensive discussions. This study, dive through the meaning of the term knowledge management and its effect on the performance of the government sector along with its impact and aspects on their performance , specifically in Dubai and from their managers point of view. The method of analytical descriptive is the one being conducted in this study to fulfill the research needs, thus make it easier to apply in the empirical studies through the framework drawn integrated approach. Following the lead of the Cronbach’s Alpha value, this study will use the questionnaire to gather the required data. In order to predict the OP, the multiple linear regression analysis was used basing on the factors KG, KSR and KST. As the result showed with 49.6 percent of the total variance in Model favored that the KG, KSR and KST were the main predictors of the OP.